2023
DOI: 10.3390/agriculture13020421
|View full text |Cite
|
Sign up to set email alerts
|

Management of Weeds in Maize by Sequential or Individual Applications of Pre- and Post-Emergence Herbicides

Abstract: Weeds impose serious problems in maize (corn) production, resulting in reduced crop yields and lower profits for farmers. The adverse effects of weeds have been attributed to the competition with maize plants for light, water, and nutrients, which can result in reduced growth and yield of the crop. In this context, effective weed management is important to minimize the negative impact of weeds on maize production. This can be achieved through a combination of cultural, mechanical, and chemical control methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…ha -1 + atrazine @ 625 g a.i ha -1 at 20 DAS (7,718 kg ha -1 ), however all were statistically on par with each other, but significantly superior over unweeded control (4,634 kg ha -1 ) (Table 4). The results obtained are in accordance with Alptekin et al (2023) [9] . The higher kernel yield in PE application of atrazine @ 1.25 kg a.i.…”
Section: Kernel Yield (Kg Ha -1 )supporting
confidence: 92%
“…ha -1 + atrazine @ 625 g a.i ha -1 at 20 DAS (7,718 kg ha -1 ), however all were statistically on par with each other, but significantly superior over unweeded control (4,634 kg ha -1 ) (Table 4). The results obtained are in accordance with Alptekin et al (2023) [9] . The higher kernel yield in PE application of atrazine @ 1.25 kg a.i.…”
Section: Kernel Yield (Kg Ha -1 )supporting
confidence: 92%
“…In the context of this study, we evaluated the safety of quinoa through herbicide immersion and greenhouse pot experiments with pre-seedling treatments. This is similar to the study conducted on maize crops by Alptekin et al [13], who evaluated the efficacy of the combined use of pre-seedling and post-seedling herbicides through field experiments. In these experiments, special attention was paid to the effects of 10 commonly used preseedling herbicides and 13 commonly used post-seedling herbicides on the safety of quinoa, as well as the safety and weed control efficacy of penoxsulam in combination with specific herbicides such as metamifop, pinpxaden, and benzobicyclon.…”
Section: Introductionsupporting
confidence: 77%
“…Building on the results of the combination safety assessments, a mixture of 5% penoxsulam OD and 10% metamifop EC was selected for laboratory bioassay activity testing on weeds at a volumetric ratio of 1:4.6. The application period was set when grassy weeds reached the 3-leaf and 1-heart stage, and broadleaf weeds reached the 4-leaf stage (BBCH stages [13][14] [19]. The cultivation method for the test materials was the same as that described in Section 2.5.2.…”
Section: Laboratory Safety Evaluation and Efficacy Of Penoxsulam Comb...mentioning
confidence: 99%
“…This substance disturbs the course of photosynthesis, chlorophyll decay and cell membrane function, leading to weed death [54]. Additionally, Alptekin et al [55] confirmed that when it is applied to the soil, it reduces the number of weeds, thus increasing the quality and quantity of maize crops. In the present study, maize responded positively to the effects of the tested herbicides, as evidenced by the obtained values of its tolerance index (TI) to these preparations.…”
Section: Response Of Maize (Zea Mays L) To Herbicidesmentioning
confidence: 99%